Quantitative evaluation of the antioxidant properties of garlic and shallot preparations - Leelarungrayub N. (2014)
Shallots and garlic are an important part of the diet of many populations and there is long-held belief in their health enhancing properties. This study tested whether fresh and commercial shallot and garlic preparations have antioxidant properties that might justify such claims.